Usage of UPI in the context of digitalization of payments in India - Knigge, Felix Alexander (2025)
The main objective of this thesis is to map the usage of the smartphone-based instant payment system UPI in India. In addition, this thesis aims to find out whether UPI shows tendencies of cannibalization of the usage of other non-cash retail payment methods. These goals are tackled by first shedding light on the characteristics of digital payments in general. Second, the specifics of payments in the Indian context are outlined, covering both the functioning of digital payments and the usage of those systems. Third, factors that contributed to the rapid adoption of UPI are presented. Fourth, the way in which UPI is being used is tackled, including its outlook and the challenges its ecosystem faces. Fifth, the impact of UPI on the usage of other non-cash retail payment methods is analyzed. The core of that analysis consists of multiple cointegration models built on monthly retail payment data.